Estimation of Anti CMV Antibodies in Iraqi Pregnant Women Infected with Chronic Cytomegalovirus - Safa A. Khudhair (Journal of Global Pharma Technology, 2018)
Cytomegalovirus (CMV) is a double-stranded DNA virus that belongs to the Herpesviridae (Herpesvirus) family, and it is the largest herpes virus in size. It affects all age groups and spreads worldwide. Human cytomegalovirus (HCMV) can cause fatal diseases to humans, and it is the most common cause of congenital birth and maternal infections. The study was conducted on 122 Iraqi pregnant women who had chronic CMV infection (with positive IgG antibodies), and 10 healthy women (with negative IgG and IgM antibodies) as control group for comparison purposes at Al-Elwiya hospital from May to August 2017. Venous blood samples were collected from the studied women to evaluate the levels of serum anti CMV IgG and IgM antibodies.  The results of the study showed that the highest antibody titers was within the age group (< 25 years) and women without previous abortion showed the highest CMV infection (55%), while no significant difference was shown between the IgG and IgM values within the categories of number of pregnancies.Keywords: CMV IgM & IgG antibodies-Pregnancy.